1996
DOI: 10.1111/j.1365-2915.1996.tb00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral sensitivity in the eyes of male and female Lutzomyia longipalpissandflies

Abstract: Using electroretinogram recordings, the response of Lutzomyia longipalpis sandfly eyes to a range of wavelengths of light was measured, and spectral sensitivity determined. The eyes of both male and female adult sandflies were found to respond maximally to light in the ultraviolet region (at 340 nm) with a secondary peak in the blue-green-yellow region at 520 nm for females and 546 nm for males. The Mann-Whitney U test showed no significant differences between males and females at corresponding wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
4
33
0
3
Order By: Relevance
“…vexator compared with the shorter wavelength blue (470 nm) and green (502 nm) lights, showing analogous attraction behavior to other dipterans. Mellor et al (1996) reported that spectral sensitivity of Lu. longipalpis was similar to that of Ae.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…vexator compared with the shorter wavelength blue (470 nm) and green (502 nm) lights, showing analogous attraction behavior to other dipterans. Mellor et al (1996) reported that spectral sensitivity of Lu. longipalpis was similar to that of Ae.…”
Section: Discussionmentioning
confidence: 98%
“…The eyes of adult Lu. longipalpis respond maximally to light in the UV region and blue-green-yellow region (Mellor et al 1996). Mellor and Hamilton (2003) provided evidence that Lu.…”
mentioning
confidence: 98%
“…Studies of sand fly vision have previously shown that both sexes of L. longipalpis are attracted to light in the UV and blue-green-yellow regions of the visual spectrum, although there is some indication that males and females differ in their responses to varying wavelengths [41,42]. Even if colour alone is not an effective attractor of sand flies, these results demonstrate that taking account of colour preferences could aid in fully optimising novel strategies for L. longipalpis control.…”
Section: Discussionmentioning
confidence: 99%
“…Lutzomyia longipalpis has eyes with a spectral sensitivity similar to that of Glossina morsitans (Mellor et al, 1996), which are known to use vision in orientation towards a host. When sand¯ies choose a host, it is thought that size is important in the recognition process (Quinnell et al, 1992).…”
Section: Introductionmentioning
confidence: 99%